ISLAM AND PROBLEMS OF STATE: CONSIDERING THE POSITION OF SHARIA IN DEMOCRATIC COUNTRY INDONESIA - Nurrohman Nurrohman (UIN Sunan Gunung Djati Bandung, 2014)
The jargon stating that humans are social beings seems to have become theproportion accepted by Islamic thinkers from past to present. Neither of the Islamicexperts refuses the fact that to be able to develop their self-potencies andhumanitarianism, human beings impossibly can live alone without requiringsomeone else’s aids or helps. However, when they talk about the relationshipbetween religion and power, Islam and politics or Islam and state, not all of theIslamic experts have the same viewpoints. Their distinction in history can be investigated from the difference among them in seeing what is the main mission brought by Prophet Muhammad, is it right that Prophet Muhammad is as the head of state? If yes, is it part of his treatise mission or part of the tactics, procedure or ijtihad (reinterpretation) in his efforts to build egalitarian society guided by the universal moral values.